The stocks and flows of nitrogen, phosphorus and potassium across a 30-year time series for agriculture in Huantai county, China - Bellarby, Jessica; Surridge, Ben W.J.; Haygarth, Philip M.; Liu, Kun; Siciliano, Giuseppina; Smith, Laurence; Rahn, Clive; Meng, Fanqiao (The Science of the total environment, 2018)
•Dynamic substance flow analysis highlight nutrient imbalances.•Revealed divergence of farm practice, fertiliser recommendations and best practice•Specific improvements in nutrient management for different systems are required.•Systemic analysis at county scale matches relevant decision making and policy.•Advice can be tailored drawing from readily available information. In order to improve the efficiency of nutrient use whilst also meeting projected changes in the demand for food within China, new nutrient management frameworks comprised of policy, practice and the means of delivering change are required. These frameworks should be underpinned by systemic analyses of the stocks and flows of nutrients within agricultural production. In this paper, a 30-year time series of the stocks and flows of nitrogen (N), phosphorus (P) and potassium (K) are reported for Huantai county, an exemplar area of intensive agricultural production in the North China Plain. Substance flow analyses were constructed for the major crop systems in the county across the period 1983–2014. On average across all production systems between 2010 and 2014, total annual nutrient inputs to agricultural land in Huantai county remained high at 18.1kt N, 2.7kt P and 7.8kt K (696kg N ha−1; 104kgP ha−1; 300kgK ha−1). Whilst the application of inorganic fertiliser dominated these inputs, crop residues, atmospheric deposition and livestock manure represented significant, yet largely unrecognised, sources of nutrients, depending on the individual production system and the period of time. Whilst nutrient use efficiency (NUE) increased for N and P between 1983 and 2014, future improvements in NUE will require better alignment of nutrient inputs and crop demand. This is particularly true for high-value fruit and vegetable production, in which appropriate recognition of nutrient supply from sources such as manure and from soil reserves will be required to enhance NUE. Aligned with the structural organisation of the public agricultural extension service at county-scale in China, our analyses highlight key areas for the development of future agricultural policy and farm advice in order to rebalance the management of natural resources from a focus on production and growth towards the aims of efficiency and sustainability. [Display omitted]